Cloning and phylogeny of endogenous retroviral elements belonging to the HERV-K LTR in cDNA library of human fetal brain and Xq21.3 region linked to psychosis - Kim, H; Crow, T (2001)
Long terminal repeats (LTRs) of the human endogenous retrovirus K family (HERV-K) have been found to be coexpressed with sequences of closely located genes. Five elements of the HERV-K LTR were identified from the cDNA library of a human fetal brain. Two of them (FB-1 and FB-5) are closely related to the human specific HERV-K LTR elements by a phylogenetic analysis. We also investigated such elements within the Xq21.3 region linked to psychosis that was replicated on the Y chromosome after the separation of the chimpanzee and human lineages. Four elements of HERV-K LTR were identified in that region. Two of these elements (K-X10-5 and K-X13-1) have a high degree of sequence similarity to the human specific HERV-K LTR. The determination of the loci of such elements and their possible relationship to other genes that have contributed to late developments in human evolution provides a strategy for investigating the role of retroviruses/retrotransposons in species-related hominid characteristics.